Resenha de: Testamenta XII Patriarcharum - Mehlmann, João (Revista de História, 1970)
JONGE (M. de). — Testamenta XII Patriarcharum. Edited According to Cambridge University Library MSS Ff. 1. 24, fol. 203a-262b with Short Notes (Pseudepigrapha Veteris Testamenti Graece. Volumen Primum), E. J. Brill, Leiden, 1964, XVIII + 86 págs.